Marketing research for a Teppanyaki restaurant in Iceland. - Telma Bergmann Árnadóttir 1986- (2011)
The focus of this thesis was to determine whether there was a potential market for a new business idea, about establishing a foreign model of a restaurant in Iceland. The model in question was the Japanese originated restaurant Teppanyaki. This restaurant form is quite well known in several countries, but has not yet been operated in Iceland and therefore its target group was unknown. To investigate the market potentiality, aspects from consumer behavior and target marketing were utilized. A market research was constructed through a questionnaire. In addition in depth interviews with experienced people in the Teppanyaki field abroad were conducted to gain a clearer vision on the subject. The results indicated a favorable market possibility for this type of a restaurant in Iceland. People of both genders in the ages between 30 and 59 years had the strongest response to be identified as Teppanyaki’s main target group.